Theory and practice of energy-focused fracturing development technology - Qingzhong ZHU; Wei XIONG; Dingwei WENG; Shuai LI; Wei GUO; Xueying ZHANG; Yuhang XIAO; Yutian LUO; Meng FAN (Petroleum Exploration and Development)
Currently, unconventional reservoirs are characterized by low single well-controlled reserves, high initial production but fast production decline. This paper sorts out the problems of energy dispersion and limited length and height of main hydraulic fractures induced in staged multi-cluster fracturing, and proposes an innovative concept of “energy-focused fracturing development”. The technical connotation, theoretical model, and core techniques of energy-focused fracturing development are systematically examined, and the implementation path of this technology is determined. The energy-focused fracturing development technology incorporates the techniques such as geology-engineering integrated design, perforation optimization design, fracturing process design, and drainage engineering control. It transforms the numerous, short and dense hydraulic fractures to limited, long and sparse fractures. It focuses on fracturing energy, and aims to improve the fracture length, height and lateral width, and the proppant long-distance transportation capacity, thus enhancing the single well-controlled reserves and development effect. The energy-focused fracturing development technology has been successfully applied in the carbonate reservoirs in buried hill, shallow coalbed methane reservoirs, and coal-rock gas reservoirs in China, demonstrating the technology’s promising application. It is concluded that the energy-focused fracturing development technology can significantly increase the single well production and estimated ultimate recovery (EUR), and will be helpful for efficiently developing low-permeability, unconventional and low-grade resources in China.